1977
DOI: 10.1177/00220345770560090701
|View full text |Cite
|
Sign up to set email alerts
|

The Strengthening of Aluminous Porcelain with Bonded Platinum Foils

Abstract: Results are presented to demonstrate the effect of bonding thin platinum foils to aluminous dental porcelain. The increased strength is explained in terms of a reduction in surface and subsurface pores in the porcelain brought about by improved wetting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…It has been also demonstrated that the addition of either metal powders or fibers reduced abrasion resistance of conventional glass-ionomer cements, perhaps due to poor bonding between the reinforcing agent and the matrix. [62][63][64][65][66] 4.1. Stainless-steel glass-ionomer cements Kerby et al prepared stainless-steel glass-ionomer cements by combining atomized stainless-steel powder with an average particle size of 9 mm with a commercially available glass-ionomer powder.…”
Section: Chemical Structure Of Set Cementmentioning
confidence: 99%
“…It has been also demonstrated that the addition of either metal powders or fibers reduced abrasion resistance of conventional glass-ionomer cements, perhaps due to poor bonding between the reinforcing agent and the matrix. [62][63][64][65][66] 4.1. Stainless-steel glass-ionomer cements Kerby et al prepared stainless-steel glass-ionomer cements by combining atomized stainless-steel powder with an average particle size of 9 mm with a commercially available glass-ionomer powder.…”
Section: Chemical Structure Of Set Cementmentioning
confidence: 99%
“…McLean and Sced4 proposed the use of tin-oxide-coated platinum foil as a reinforcing mechanism for porcelain jacket crowns. To confirm this, Sced et al 5 fabricated disc specimens for transverse testing. These were 1 5 mm in diameter and were tested on a circular knife edge support.…”
Section: Introductionmentioning
confidence: 97%
“…It reduces surface and subsurface porosity in the porcelain and has the high strength of aluminous porcelain. 31,32 • Twin foil technique involves laying down of two platinum foils in close opposition to each other. One foil provides a matrix for the bonding of the porcelain which is removed after baking.…”
Section: Enamelling Of Metalsmentioning
confidence: 99%